2017
DOI: 10.1111/jam.13408
|View full text |Cite
|
Sign up to set email alerts
|

Thyme essential oil as an alternative mechanism: biofungicide-causing sensitivity ofMycosphaerella graminicola

Abstract: These findings will probably be useful to design an alternative biofungicide which will not lead to pathogen multidrug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 32 publications
0
7
0
2
Order By: Relevance
“…These effects have been attributed to the hydroxyl groups and the presence of a system of delocalized electrons on the monoterpens thymol and carvacrol and other phenolic compounds (Ultee, Bennik, & Moezelaar, ). In addition, Ben Jabeur, Somai‐Jemmali, and Hamada () have shown that thymol has a role in specific genes associated with fungal development.…”
Section: Resultsmentioning
confidence: 99%
“…These effects have been attributed to the hydroxyl groups and the presence of a system of delocalized electrons on the monoterpens thymol and carvacrol and other phenolic compounds (Ultee, Bennik, & Moezelaar, ). In addition, Ben Jabeur, Somai‐Jemmali, and Hamada () have shown that thymol has a role in specific genes associated with fungal development.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the chemical composition of essential oils is affected by several factors, such as species, seasonality, plant age, and geographic location, as well as the extraction method [ 27 ]. For example, the composition of the essential oil of Thymus vulgaris varies both qualitatively and quantitively among plants collected from different geographical locations (Spain, Serbia, and Tunisia) and was investigated by Valcárcel et al [ 28 ], Sarić-Krsmanović et al [ 29 ], and Ben Jabeur et al [ 30 ].…”
Section: Mediterranean Plants That Have Been Recently Investigated Fo...mentioning
confidence: 99%
“…When it is applied against bacteria, carvacrol can influence virulence factors, including reduced toxin production and biofilm formation by the bacteria. Most recent studies indicated that carvacrol affects gene expression [13,14] and subsequently reduces virulence of microorganisms [15,16,17].…”
Section: Antimicrobial Activity Of Carvacrol and Associated Mechanmentioning
confidence: 99%